Revision of Legislation Regarding the Accountability of Notaries for Documents Executed Beyond the Office Premises to Ensure Fair and Certain Legal Provision - Muhammad Idris Assaf; Adi Sulistiyono; Endang Pandamdari (LAW & PASS: International Journal of Law, Public Administration and Social Studies, 2024)
Paragraph (1) of Law No. 2 of 2014, modified by Law No. 30 of 2004, stipulates that Notaries are forbidden from reciting documents beyond their designated jurisdiction. An issue arises where Notaries who have indeed recited deeds outside their scope of work have not faced repercussions in accordance with the pertinent legal framework. The methodology employed in this research is that of normative jurisprudence, involving an examination of secondary data sources, particularly primary legal documents such as statutory provisions, and secondary legal sources like books, articles, or journals. The theoretical framework utilized is that of equitable law certainty. Findings reveal a consistent failure to penalize Notaries who have transgressed by reciting deeds outside their designated area, despite clear violations of regulations outlined in the UUJN. In judicial rulings, authentic deeds recited by Notaries beyond their jurisdiction remain valid, highlighting the inadequacy of existing enforcement mechanisms. Drawing a comparison with the regulations governing Notaries in the Netherlands, it is evident that revisions to Article 17 (1) and (2), Article 19 paragraph (2), and Article 9 (1) letter d of the Law of Judgment are imperative to ensure the establishment of a fair and certain legal system as mandated by Article 28 D Paragraph (1) of the 1945 Constitution. Such reforms are essential to empower legal authorities in executing their duties effectively, serving the interests of justice seekers, and eliminating any ambiguity surrounding the recitation of deeds by Notaries beyond their jurisdiction.